2012
DOI: 10.1097/ccm.0b013e318232e404
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for matrix metalloproteinase-8 in sepsis*

Abstract: Objectives Matrix metalloproteinase-8 (MMP-8) mRNA expression was previously found to be increased in whole blood of children with septic shock. The impact of this finding on the severity and inflammatory response to sepsis is unknown. Here, we investigate the relationship between MMP-8 and disease severity in a children with septic shock. We further corroborate the role of MMP-8 in sepsis in a murine model. Design Retrospective observational clinical study and randomized controlled laboratory experiments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 32 publications
2
106
3
1
Order By: Relevance
“…IL-1R2 is a decoy receptor for IL-1 and highlights the tightly regulated activity of IL-1 in neonates (21). Several innate immunityrelated genes with biology significance were represented among the top 10 in three of the four infected groups, including MMP-8 (metalloproteinase-8, a neutrophil-derived collagenase involved in the degradation of type I collagen [22]), olfactomedin 4 (OLFM4; present in neutrophil granules [23] and potentially important in neutrophil extracellular trap [NET] formation [24]), membranespanning 4-domains, subfamily A, member 4A (MS4A4A; tetraspanin; important for cell migration [25]) and IL-18R1 (receptor for proinflammatory cytokine IL-18 [21] and also ranked eleventh in the early sepsis group). Top downregulated genes were far more varied among groups compared with those that were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…IL-1R2 is a decoy receptor for IL-1 and highlights the tightly regulated activity of IL-1 in neonates (21). Several innate immunityrelated genes with biology significance were represented among the top 10 in three of the four infected groups, including MMP-8 (metalloproteinase-8, a neutrophil-derived collagenase involved in the degradation of type I collagen [22]), olfactomedin 4 (OLFM4; present in neutrophil granules [23] and potentially important in neutrophil extracellular trap [NET] formation [24]), membranespanning 4-domains, subfamily A, member 4A (MS4A4A; tetraspanin; important for cell migration [25]) and IL-18R1 (receptor for proinflammatory cytokine IL-18 [21] and also ranked eleventh in the early sepsis group). Top downregulated genes were far more varied among groups compared with those that were upregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Solan et al (2012) reported that MMP8 inhibition can improve outcome in experimental sepsis. Moreover, serum MMP8 levels at admission to intensive care unit were high among sepsis patients with fatal outcome (Lauhio et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, they are involved in several inflammatory diseases (Wielockx et al, 2001;Vanlaere and Libert, 2009;Dejonckheere et al, 2011b;Vandenbroucke et al, 2011). Solan et al (2012) recently reported that MMP8 inhibition can improve outcome in experimental sepsis. Moreover, serum MMP8 levels at admission to intensive care units were high among sepsis patients with fatal outcome (Lauhio et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…14,36 Furthermore, in a murine model of sepsis, either genetic or pharmacologic inhibition of MMP8 activity significantly increased survival rates. 37 MMPs play an important role in the remodeling of a number of tissues. These enzymes are the only ones capable of degrading the components of the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%